Characteristics of Women Receiving Emergency Caesarean Section: A Cross‑Sectional Analysis from Ghana and Dominican Republic - Adu‑Bonsafoh, K.; Tunçalp, Ӧ.; Castro, A. (Springer, 2021)
Background:Significant inequalities still exist between low- and high-income countries regarding access to optimum emergency obstetric care including life-saving emergency caesarean section. These relationships are considerably stronger between population-based caesarean section rates and socio-economic characteristics with poorest households experiencing significant unmet needs persistently. Objective: To explore the characteristics of women receiving emergency C-section using a new, validated definition in Ghana and the Dominican Republic. Materials and Methods: This was a cross-sectional study conducted in Ghana and the Dominican Republic. Multivariable logistic regression analysis was used to determine women’s characteristics associated with emergency C-section. Results: This analysis included 2166 women who had recently delivered via C-section comprising 653 and 1513 participants from Accra and Santo Domingo, DR, respectively. Multivariable analyses showed that women, both in Ghana and the DR, were more likely to have an emergency C-section if they did not have a previous C-Section (adjusted Odds Ratio (aOR): 2.45, 95% CI [1.57–3.81]; and aOR: 15.5, 95% CI [10.5–22.90], respectively) and if they were having their frst childbirth, compared to women with previous childbirth (aOR: 1.77, 95%CI [1.13–2.79]; and aOR: 1.46, 95%CI [1.04–2.04], respectively). Also, preterm birth was associated with significantly decreased likelihood of emergency C-section compared with childbirth occurring at term in both Ghana and the DR (aOR: 0.31, 95%CI [0.20–0.48]; and aOR: 0.43, 95%CI [0.32–0.58], respectively). Among the Ghanaian participants, having an emergency C-section was positively associated with being referred and negatively associated with being older than 35 years of age. Characteristics such as education, religion, marital status, and residence did not differ between women’s emergency versus non-emergency C-section status. Conclusion Emergency C-section was found to be significantly higher in women with no prior C-section or those having their first births but lower in those with preterm birth in both Ghana and the DR. Data from additional countries are needed to confirm the relationship between emergency C-section status and socio-economic and obstetric characteristics, given that the types of interventions required to assure equitable access to potentially life-saving C-section will be determined by how and when access to care is being denied or not available.
Research Article
Keywords: Emergency; Access; Caesarean section; Ghana; Dominican Republic